Investigations into the Peroxidase Activity of Ferriprotoporphyrin IX and its Complexes with Clinically Relevant Antimalarial Drugs - Sammy, Chandre Jade (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.